Visual semiotic analysis of Nusantara cultural elements in the Aniwayang Desa Timun animation opening song - Daru Ramadinoto, Raden; Wiba Pamela, Apsari; Rachmawati, Rizka (Universitas Indraprasta PGRI, 2025)
This study is motivated by concerns over the erosion of local cultural values among Indonesian youth due to the massive influx of foreign popular culture. Meanwhile, Aniwayang Studio has successfully adapted traditional wayang culture into a contemporary medium of animation. This innovative success is validated by significant global achievements, including appearances at the World Osaka Expo 2025 and the Kineko International Children's Film Festival in Japan, alongside recognition and support from the Indonesian Ministry of Education and Culture. Employing a qualitative descriptive method and the Charles Sanders Peirce semiotic approach the research seeks to understand how the studio adapts wayang and Nusantara culture by analyzing the visual and auditory signs within the animation. Data were collected through observation and documentation of the “Opening Song” episode of Serial Desa Timun. The findings indicate that the visual design, including the two-dimensional profiled characters, batik motifs, and a limited black color palette on a cream-brown background, effectively function as icons and indices of traditional wayang kulit (shadow puppet) theater. The appearance of various objects, along with the use of gamelan music acts as a strong index and symbol of Nusantara cultural heritage. The analysis suggests that the animation recontextualizes traditional wayang elements into a modern, accessible, and culturally rich format. The study concludes that this innovative approach positions